Shifts between pro-inflammatory and anti-inflammatory profiles in pregnant mares: a review of physiological functions - Satué, Katiuska; La Fauci, Deborah; Medica, Pietro; Damiá Gímenez, Elena; Cravana, Cristina; Fazio, Esterina (Frontiers in Veterinary Science, 2025)
Pregnancy in the mare presents a unique immunological challenge, requiring a finely tuned balance between pro-inflammatory and anti-inflammatory responses to ensure reproductive success. Throughout gestation, the maternal immune system undergoes dynamic adaptations to support key reproductive events from conceptus mobility and fixation to the formation and function of endometrial cups, and the expansion of immunoregulatory cells that promote maternal-fetal tolerance. In early pregnancy, a controlled pro-inflammatory environment facilitates critical processes such as embryo migration and implantation. As gestation progresses, the immune profile shifts toward a tolerogenic state, marked by the proliferation of regulatory T cells (Tregs) and the activity of tolerogenic antigen-presenting cells. These adaptations protect the semi-allogeneic conceptus and sustain pregnancy. Toward term, a resurgence of pro-inflammatory signaling becomes essential to initiate parturition, activating pathways that promote uterine contractility, cervical ripening, and fetal expulsion—demonstrating that inflammation is not only a threat but a physiological necessity. Disruptions in this immunological balance whether due to excessive inflammation or insufficient tolerance can compromise embryonic and fetal viability, increasing the risk of pregnancy loss. Therefore, a comprehensive understanding of the immunological and inflammatory mechanisms throughout equine gestation is essential to advance reproductive physiology and improve clinical strategies for fertility management in mares.